Atomically Dispersed ZnN5 Sites Immobilized on g‐C3N4 Nanosheets for Ultrasensitive Selective Detection of Phenanthrene by Dual Ratiometric Fluorescence. Issue 15 (4th March 2023) - Qu, Binhong; Li, Peng; Bai, Linlu; Qu, Yang; Li, Zhijun; Zhang, Ziqing; Zheng, Bing; Sun, Jianhui; Jing, Liqiang
Abstract: Ultrasensitively selective detection of trace polycyclic aromatic hydrocarbons (PAHs) like phenanthrene (PHE) is critical but remains challenging. Herein, atomically dispersed Zn sites on g‐C3 N4 nanosheets (sZn‐CN) are constructed by thermal polymerization of a Zn–cyanuric acid–melamine supramolecular precursor for the fluorescence detection of PHE. A high amount (1.6 wt%) of sZn is grafted in the cave of CN with one N vacancy in the form of unique Zn(II)N5 coordination. The optimized sZn‐CN achieves a wide detection range (1 ng L −1 to 5 mg L −1 ), ultralow detection limit (0.35 ng L −1, with 5‐order magnitude improvement over CN), and ultrahigh selectivity toward PHE even among typical PAHs based on the built PHE‐CN dual ratiometric fluorescence method. By means of in situ Fourier transform infrared spectroscopy, time‐resolved absorption and fluorescence spectroscopy, and theoretical calculations, the resulting superior detection performance is attributed to the favorable selective adsorption of PHE on as‐constructed atomic Zn(II)N5 sites via the ionic cation–π interactions (Zn δ+ C2 δ− type), and the fluorescence quenching is dominated by the inner filter effect (IFE) from the multilayer adsorption of PHE at low concentrations, while it is done by the protruded photogenerated electron‐transfer process, as well as IFE from the monolayer adsorption of PHE at ultralow concentration. Abstract : Atomically dispersed Zn(II)N5 sites are immobilized on g‐C3 N4 nanosheets for detecting phenanthrene (PHE) by dual ratiometric fluorescence with ultrahigh sensitivity (limit of detection = 0.35 ng L −1 ) and selectivity among typical polycyclic aromatic hydrocarbons due to favorable selective adsorption of PHE on as‐constructed atomic Zn(II)N5 sites via the ionic cation –π interactions (Zn δ+ C2 δ− type).